2012
DOI: 10.1080/87567555.2012.697081
|View full text |Cite
|
Sign up to set email alerts
|

Writing to Learn: Benefits and Limitations

Abstract: Writing to learn (WTL) is the act of making a subject or topic clear to oneself by reasoning through it in writing; it is a pedagogical approach that uses writing to facilitate learning (Zinsser 1988). Some researchers have reported favorable results associated with the approach (Balgopal and Wallace 2009; Bullock 2006; Hand, Hand, Gunel, and Ulu 2009). However, others have indicated that studies supporting WTL pedagogy tend to lack comparison groups, pre/posttest data, or the rich description that contributes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 10 publications
(10 reference statements)
1
13
0
5
Order By: Relevance
“…2 (2016) 653-668 del conocimiento. Consideramos que lo anterior es una diferencia clave entre la presente propuesta de escribir para aprender y las actividades que típicamente se proponen a los estudiantes en esta línea pedagógica, en la que se solicita redactar textos para reflexionar sobre algún contenido de aprendizaje, sin atender las exigencias de un género discursivo particular, ni de una audiencia concreta (Fry y Villagomez, 2012;Nevid, Pastva, McClelland, 2012;Nückles, Hubner y Renkl, 2009;Tracie, Stewart, Myers, y Culley, 2010). A nuestro juicio, dichas actividades, aunque valiosas, no explotan todo el potencial de la escritura como herramienta de aprendizaje ya que se centran en reflexionar sobre lo que ya se sabe, más que en generar significado en torno a ese conocimiento.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…2 (2016) 653-668 del conocimiento. Consideramos que lo anterior es una diferencia clave entre la presente propuesta de escribir para aprender y las actividades que típicamente se proponen a los estudiantes en esta línea pedagógica, en la que se solicita redactar textos para reflexionar sobre algún contenido de aprendizaje, sin atender las exigencias de un género discursivo particular, ni de una audiencia concreta (Fry y Villagomez, 2012;Nevid, Pastva, McClelland, 2012;Nückles, Hubner y Renkl, 2009;Tracie, Stewart, Myers, y Culley, 2010). A nuestro juicio, dichas actividades, aunque valiosas, no explotan todo el potencial de la escritura como herramienta de aprendizaje ya que se centran en reflexionar sobre lo que ya se sabe, más que en generar significado en torno a ese conocimiento.…”
Section: Discussionunclassified
“…(Gradwohl Nash y Schumacher, 1991;Kieft, Rijlaarsdam, van den Bergh, 2008;Kieft, Rijlaarsdam y van den Bergh, 2006;Newell, 2006;Tynjälä, 1998). Esto se debe, por una parte, a que son escasos los estudios que miden de manera rigurosa (pre/postest) resultados entre grupos de comparación y, por otra, a que solo en algunas ocasiones se reportan diferencias estadísticamente significativas entre los grupos (Fry y Villagomez, 2012).…”
unclassified
See 1 more Smart Citation
“…Even though children in upper elementary school are expected to produce a wide variety of increasingly complex texts (Pytash & Morgan, 2014), students most often engage in writing to learn (Gilbert & Graham, 2010). Writing to learn is a term used to describe the use of writing as a thinking tool to enhance one's own understanding of a topic (Fry & Villagomez, 2012). While some research has demonstrated the benefits of writing to learn to enhance student learning in the content areas (Bangert-Drowns, Hurley, & Wilkinson, 2004), writing to learn tasks do not usually focus on apprenticing students into learning to negotiate different text genres.…”
Section: Classroomsmentioning
confidence: 99%
“…Broadly speaking, students' scientific writing assignments can be categorized as "learning to write" (LTW), where the primary emphasis is on communicating effectively, or as "writing to learn" (WTL), where writing is used more as a tool for learning content (Reynolds et al 2012). For WTL advocates, writing is not merely a process of reporting what the writer already knows, but deepening one's understanding of a topic while attempting to write about it (Fry and Villagomez 2012). To the extent that LTW can be distinguished from WTL, we will focus primarily on the latter.…”
Section: Introductionmentioning
confidence: 99%